DETERMINATION OF PUNISHMENT FOR AGGREGATION OF CRIMINAL OFFENCES - Persidskis, Ainārs (Administrative and Criminal Justice, 2015)
The purpose of the article is to identify the problems related with signs of conceptual aggregation of criminal offences, find the problems and offer possible solutions. The actuality of article – signs of conceptual aggregation of criminal offences people understand different, because they have different views about the origins of conceptual aggregation of criminal offences. The author concludes that some of the signs of conceptual aggregation of criminal offences are general, mislead and does not comply with conceptual aggregation of criminal offences.